2000
DOI: 10.1002/(sici)1097-4636(200005)50:2<138::aid-jbm7>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Human chondrocyte proliferation and matrix synthesis cultured in Atelocollagen� gel

Abstract: To evaluate the potential of Atelocollagen gel as a carrier for chondrocyte transplantation, histological and biochemical characteristics of the chondrocytes in gel culture were compared with those in conventional monolayer cultures. Articular chondrocytes from 20 patients were isolated by enzyme digestion, embedded in Atelocollagen gel, and cultured for up to 4 weeks. The effects on proliferation, morphological changes, and synthesis of proteoglycans were analyzed by cell counts, light and electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 38 publications
4
63
1
2
Order By: Relevance
“…Interaction of this subunit with collagen type I leads to osteoblastic differentiation of MSCs, which is a crucial event in the expression of the osteogenic phenotype (Mizuno et al, 2000). Chondrocytes cultured in collagen type I gel grew in three dimensions, accumulating a cartilaginous ECM while maintaining their round morphology during the culture period (Kimura et al, 1987;Uchio et al, 2002). Furthermore, a cartilage defect was partially repaired when human autologous culture-expanded MSCs engineered in a collagen type I gel were transplanted into an osteoarthritic knee (Wakitani et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of this subunit with collagen type I leads to osteoblastic differentiation of MSCs, which is a crucial event in the expression of the osteogenic phenotype (Mizuno et al, 2000). Chondrocytes cultured in collagen type I gel grew in three dimensions, accumulating a cartilaginous ECM while maintaining their round morphology during the culture period (Kimura et al, 1987;Uchio et al, 2002). Furthermore, a cartilage defect was partially repaired when human autologous culture-expanded MSCs engineered in a collagen type I gel were transplanted into an osteoarthritic knee (Wakitani et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…6 Our previous in vitro study in which human articular chondrocytes were used also showed that chondrocytes in a monolayer culture differentiated into fibroblast-like cells and synthesised chondroitin-4-sulphatedominant proteoglycans. 25 By contrast, chondrocytes cultured in atelocollagen gel maintained the chondrocyte phenotype and synthesised a chondroitin-6-sulphate-rich matrix. In addition, Coon and Cahn 35 reported that dedifferentiated chondrocytes, during four successive clonal passages in monolayer culture, re-expressed chondrocyte phenotypes when they were in contact with normal chondrocytes or were in the presence of unknown highmolecular-weight molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Auch als dreidimensionales Kultivierungssystem haben Kollagenmatrices im Rahmen von MACT-Verfahren einen klinischen Stellenwert (Andereya et al, 2006;Andereya et al, 2007). Kollagengelmatrices stimulieren die zelluläre Proliferation und Syntheseleistung in vitro (Schuman et al, 1995;Uchio et al, 2000) und stellen damit zumindest in vielerlei Hinsicht eine funktionelle Extrazellulär-matrix-Umgebung dar, die hyalinem Knorpel ähnlich ist (Schneider et al, 2003) und…”
Section: 22) Typ-i-kollagenmatrizes In Der Knorpelregenerationunclassified